BENTUK-BENTUK SAPAAN FILM FOUR BROTHERS KARYA HENRY HATHAWAY - RUMENGAN, BRYAN CYBERT VICTORY (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT Linguistics is a study of language, one of its sub-field is sociolinguistics that deals with a speaker as the member of society.In other words, sociolinguistics studies about aspects of language in society, especially the variation which consists in the language related with the factors of society. One of sociolinguistic parts is Kinship terms that talk about human relations, one of its subjects is system of address. Addressing is an important aspect in discourse which can not be overlooked. In doing this research, the writer formulated the research question; what kinds of address and how are they used by the characters in the movie Four Brothers? The objectives of this research were to identify and describe terms of address in the movie of Four Brothers by Henry Hathaway. This research used descriptive method. Data were taken from utterances which contained address terms that were used by the characters in the movie. The collected data were identified and analyzed based on Ervin-Tripp?s theory. The result shows thatterms of address which are used by the characters in the movie of Four Brothers by Henry Hathaway are referred to Ervin-Tripp?s theory (alternation principle). Addresses which were used by the characters had various forms, they were influenced by status, rank, identity and degree of generation in society. This research is expected to give information about the terms of address in the movie of Four Brothers and give information and also knowledge for the reader about term of address. Keywords : Linguistics, Sociolinguistics, Terms of Address, Alternation Principle.